On Some Transforming Elements of Traditional Yezidi Weddings Performed in Armenia - Tereza Amryan (Banber Arevelagitut'yan Instituti, 2025)
The Yezidi wedding, due to its unique and different colours and elements, has been a subject of interest for their non-Yezidi neighbors. From time to time, it has been an object of interest for journalists, researchers and scientists as well. However, the transforming elements of the Yezidi traditional wedding have not been properly studied as of yet. In the framework of this article, some elements of Yezidi traditional weddings are examined: those elements have undergone various transformations due to external influences over the last few decades. The wedding ceremony is a more open, easily influenced and transformable ritual. Therefore, many elements of the traditional Yezidi wedding have partly been influenced by the Armenian wedding ritual and partly influenced by modern wedding trends. Many elements have been given a new appearance and interpretation, while some old ceremonies have been reborn and are performed in a new way. Additionally, some traditional forms of marriage (polygamy, levirate) have been forgotten among the Yezidis of Armenia. The study of the transformation of some elements of the traditional Yezidi wedding is important, as it can greatly contribute to the study of the dynamics of other ethnic transformative processes.